2020
DOI: 10.1136/bmj.m545
|View full text |Cite
|
Sign up to set email alerts
|

What role should the commercial food system play in promoting health through better diet?

Abstract: Martin White and coauthors consider that the commercial food system has the potential to show leadership and support for dietary public health, but systemic change is needed first and this is likely to require governmental action

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 63 publications
0
62
0
1
Order By: Relevance
“…For instance, when we focus on a single RFE goal and ignore that other outcomes are produced, we create solutions that may address our goal but simultaneously produce harm in other areas. Such consequences may be unintentional or well-known (e.g., promotion of unhealthy, processed foods which increase profits, but are associated with non-communicable disease [ 130 , 131 , 132 ]). Yet, moving forward it may be important to reframe these varying outcomes from inevitable systemic trade-offs to sites of opportunity.…”
Section: Population Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when we focus on a single RFE goal and ignore that other outcomes are produced, we create solutions that may address our goal but simultaneously produce harm in other areas. Such consequences may be unintentional or well-known (e.g., promotion of unhealthy, processed foods which increase profits, but are associated with non-communicable disease [ 130 , 131 , 132 ]). Yet, moving forward it may be important to reframe these varying outcomes from inevitable systemic trade-offs to sites of opportunity.…”
Section: Population Outcomesmentioning
confidence: 99%
“…Working together will also push discipline-centric change agents to consider the feasibility and sustainability of their proposed solutions and may help spur the creation of more worthwhile and effective transformations. While collaboration and attention to multiple outcomes will be easy for some, other groups may require support or even accountability measures to help cultivate “common ground” (e.g., reframing from businesses profitability to sustainability), and many have already been calling for and provided specific strategies to do so [ 115 , 129 , 131 , 133 ].…”
Section: Population Outcomesmentioning
confidence: 99%
“…They are producing greater amounts of more affordable and accessible food for our expanding population, but at the cost of our health 1. As White and colleagues note, “the commercial food system has the potential to show leadership and support for dietary public health, but systemic change is needed first and this is likely to require governmental action.”3…”
Section: Power Of “Big Food”mentioning
confidence: 99%
“…White et al recently analyzed the role commercial food systems should play in positively affecting health through diet. 7 The authors concluded that to make food systems more sustainable for both human and planetary health, a change to the entire global food system is required, and that governments have the ability to speed up this change. Collective action must be taken so that the differences between what large and small-scale producers face with their respective abilities to adapt to climate change, in addition to social or health shocks, do not inadvertently create greater socioeconomic inequality and vulnerability.…”
mentioning
confidence: 99%